Efektifitas Proses Rekruitment SDM Perawat Bedah Di Rumah Sakit Umum Pekerja . - Riadi, Eka; Wiyono, Witji; Suryati, Adelina (CV. ITTC INDONESIA, 2024)
In the recruitment process in the operating room, it is necessary to quickly attract human resources, so the author conducted research on